2019
DOI: 10.12659/msm.913351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cervical Rotatory Manipulation on Internal Carotid Artery in Hemodynamics Using an Animal Model of Carotid Atherosclerosis: A Safety Study

Abstract: Background Spinal manipulation, particularly in cervical rotatory manipulation (CRM), has become increasingly popular in physical therapies, with satisfying effect. However, it is still unclear whether CRM affects internal carotid arteries (ICA) with mild carotid atherosclerosis (CAS), especially in hemodynamics. Material/Methods Nine cynomolgus monkeys were randomly divided into 3 groups: the CAS-CRM, the CAS, and the blank control groups. CAS models were developed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…René Jonas et al 11 studied the influence of the functional structure of the cervical spine on its kinematic behavior. Guan et al 12 found in animal studies that cervical rotation manipulation does not adversely affect blood cells and is a relatively safe technique. With the wide application of finite element technology in the field of biomechanics, high‐quality calculation models provide a new method for solving the biomechanical effects of CRM.…”
Section: Introductionmentioning
confidence: 99%
“…René Jonas et al 11 studied the influence of the functional structure of the cervical spine on its kinematic behavior. Guan et al 12 found in animal studies that cervical rotation manipulation does not adversely affect blood cells and is a relatively safe technique. With the wide application of finite element technology in the field of biomechanics, high‐quality calculation models provide a new method for solving the biomechanical effects of CRM.…”
Section: Introductionmentioning
confidence: 99%